Validity and reliability of measures of television viewing time and other non-occupational sedentary behaviour of adults: A review - Clark, B.; Sugiyama, T.; Healy, Genevieve; Salmon, J.; Dunstan, D.; Owen, N. (Wiley-Blackwell Publishing Ltd., 2009)
Time spent in non-occupational sedentary behaviours (particularly television viewing time) is associated with excess adiposity and an increased risk of metabolic disorders among adults; however, there are no reviews of the validity and reliability of assessing these behaviours. This paper aims to document measures used to assess adults' time spent in leisure-time sedentary behaviours and to review the evidence on their reliability and validity. Medline, CINAHL and Psych INFO databases and reference lists from published papers were searched to identify studies in which leisure-time sedentary behaviours had been measured in adults. Sixty papers reporting measurement of at least one type of leisure-time sedentary behaviour were identified. Television viewing time was the most commonly measured sedentary behaviour. The main method of data collection was by questionnaire. Nine studies examined reliability and three examined validity for the questionnaire method of data collection. Test-retest reliabilities were predominantly moderate to high, but the validity studies reported large differences in correlations of self-completion questionnaire data with the various referent measures used. To strengthen future epidemiological and health behaviour studies, the development of reliable and valid self-report instruments that cover the full range of leisure-time sedentary behaviour is a priority. © 2008 The Authors.